ANALISIS PENGARUH CAR, LOAN, GDP DAN INFLASI TERHADAP PROFITABILITAS BANK DI INDONESIA - Sorongan, Fangky A. (Universitas Katolik Indonesia Atma Jaya, 2017)
This research aim to re-examine the relationship between bank profitability and its influence factors in banking system in Indonesia. We used ten banks who had biggest assets as a population and samples for this research: BRI, Mandiri Bank, BCA, BNI, CIMB Niaga, BTN, Panin Bank, Permata Bank, Maybank, and Danamon Bank with the interval observation 2012 to 2015. As a dependent variable is ROA as a profitability proxy, the independent variables are CAR (capital adequacy ratio), LOAN, GDP (gross domestic product) and inflation. The regression result shows CAR, LOAN, GDP have an important contribution  and significant to profitability (ROA) in bank in Indonesia, whereas the inflation variable has unsignificant influence and negative to profitability (ROA).